Corak Moderasi Pesantren di Indonesia: Studi Terhadap Persepsi dan Respon Kyai, Guru dan Santri - Andy Hadiyanto; Yusuf Hanafi; Rudy Muhamad Barnannsyah; Cendra Samitri; Siti Maria Ulfah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
Religious moderation is actually an effort to restore understanding and application of religious teachings that are sincere, friendly, and oriented towards improving the quality of life and humanity. The realization of religious moderation is expected to further strengthen the role of religion as the spirit of civilization. Pesantren as one of the oldest religious educational institutions in Indonesia, from the beginning has played a role in creating Indonesian Islamic civilization with its characteristics that are open, tolerant, and humanist. Thus, pesantren is an Islamic educational institution that has long played a role in mainstreaming moderation in Indonesia. In line with that, this study seeks to dig deeper into the mode of religious moderation that is maintained in the pesantren environment based on the perceptions and roles of the main elements of the pesantren, such as kyai, teachers, and santri. This study uses a qualitative approach by conducting a literature study and documentation of partners which can be used as a valid data source. Theoretically, the mode of religious moderation in pesantren can be seen from theological aspects, sharia, state politics, and relations with others. The results show that the manifestation of religious moderation in the theological aspect which is manifested by the aqidah ahlussunnah wal Jama'ah (aswaja), is related to the problem of human and God relations, the limitations of Mu'min Kafir, and the position of reason and revelation. In the Sharia aspect, religious moderation appears in the acceptance of mu'tabarah schools of jurisprudence, although there are still Shafii schools and reject mixing (talfiiq). In the aspect of state politics, religious moderation of kyai, ustaz, and santri can be seen in their acceptance of the Unitary State of the Republic of Indonesia (NKRI) and Pancasila as the basis of the state, and in them against the politicization of religion. As for the relationship with the moderating attitude of pesantren exponents from their acceptance of the concept seen as different attitudes and readiness to blend in without having to negate each other and lose their identity.